2021
DOI: 10.3389/fphys.2021.805148
|View full text |Cite
|
Sign up to set email alerts
|

Properties, Structures, and Physiological Roles of Three Types of Anion Channels Molecularly Identified in the 2010’s

Abstract: Molecular identification was, at last, successfully accomplished for three types of anion channels that are all implicated in cell volume regulation/dysregulation. LRRC8A plus LRRC8C/D/E, SLCO2A1, and TMEM206 were shown to be the core or pore-forming molecules of the volume-sensitive outwardly rectifying anion channel (VSOR) also called the volume-regulated anion channel (VRAC), the large-conductance maxi-anion channel (Maxi-Cl), and the acid-sensitive outwardly rectifying anion channel (ASOR) also called the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 130 publications
(206 reference statements)
1
5
0
Order By: Relevance
“…Apoptotic volume decrease (AVD) is one of the earliest events during apoptosis; the RVD machinery and the underlying ion channels (especially, VSOR) are activated by pro-apoptotic signaling pathways even under normotonic conditions (18,21,(41)(42)(43). Therefore, the blocking effects of pinocembrin on RVD and VSOR channels are expected to suppress apoptosis as we have actually observed in our experiments for the combined effects of DX and the flavonoid.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Apoptotic volume decrease (AVD) is one of the earliest events during apoptosis; the RVD machinery and the underlying ion channels (especially, VSOR) are activated by pro-apoptotic signaling pathways even under normotonic conditions (18,21,(41)(42)(43). Therefore, the blocking effects of pinocembrin on RVD and VSOR channels are expected to suppress apoptosis as we have actually observed in our experiments for the combined effects of DX and the flavonoid.…”
Section: Discussionsupporting
confidence: 66%
“…Patch-clamp studies have revealed the presence of two volume-regulated anion channels important for the CVR response to the hypoosmotic stress: the volume-sensitive outwardly rectifying Clchannel (VSOR) and the maxi-anion channel of Maxi-Cl phenotype (14). In addition to its involvement in the CVR, the VSOR serves as a pathway for releasing glutathione from thymocytes into the extracellular matrix (15), whereas the Maxi-Cl channel is known as a pathway for adenosine triphosphate (ATP) and other signaling molecules (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this hypothesis, we may assume that recently identified VSOR-inhibitors of plant origin, such as flavonoids (41) and tannins (42), could also be able to modulate the osmoresistivity of the RBC. In addition, GL and its derivatives are expected to have an impact on the cell death induction and protection in other cell types, in which VSOR plays a critical role (43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a prerequisite role of LRRC8A in VSOR/VRAC activity was confirmed in mouse cells [ 40 , 75 , 121 , 122 ], in rat cells [ 123 , 124 ], in chicken cells [ 10 ], and in zebrafish cells [ 125 ]. Recent cryo-EM studies demonstrated that not only LRRC8A [ 126 130 ] but also another LRRC8 member, LRRC8D [ 131 ], form homo-hexameric structures consisting of the transmembrane pore domain, as depicted in Fig. 2 for LRRC8A.…”
Section: Molecular Entities Of Vsor/vracmentioning
confidence: 99%